Factors influencing teachers' behavioral intention and utilization of Madrasati in public schools in Riyadh, Saudi Arabia - Alharbi, Hamad Muaybid A (2022)
Modern-day technology in the Kingdom of Saudi Arabia (KSA) is being continuously provided across schools. The utilization of Madrasati (M) as a learning management system (LMS) among teachers in public schools in Riyadh has recently attracted attention because of its role in improving the quality of the educational system in KSA. However, the key problem is the low acceptance and utilization of M LMS among teachers in KSA, particularly in Riyadh. The satisfactory teacher’s behavioral intention (BI) toward accepting and utilizing M LMS technology is still a challenge in Riyadh. There is little or no specific research report on the adoption of M LMS in intermediate and secondary schools in Riyadh. Therefore, this study investigates the factors influencing teachers’ BI and the utilization of M LMS in Saudi public schools by employing the survey method based on the quantitative approach. The factors selected to determine teachers’ BI on M LMS utilization are performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), attitudes, and competence. The questionnaire copies were distributed to 374 Saudi teachers from different schools using simple random sampling. Various statistical analyses were used to validate the data, including reliability and validity of the instrument, pilot test, data normality, descriptive analysis, structural equation modeling (SEM) using AMOS software, CFA, measurement model, path analysis, and mediation analysis. The results of SEM regarding the influence of BI on PE, EE, SI, FC, attitude, and competence indicated that the PE construct has a positive and statistically significant effect on M LMS utilization. Meanwhile, EE has a positive and significant effect on M LMS. Similarly, the relationships between SI and M LMS utilization, FC and M LMS utilization, as well as competence and M LMS utilization are also significant. The results indicate that the alternative hypotheses were accepted. On the contrary, the relationship between attitude and M LMS utilization is not significant, and the null hypothesis is accepted. The results of the mediating effect showed that PE, SI, FC, and competence have an indirect effect on M LMS utilization through the mediating role of BI. BI is statistically significant and partially mediates the relationship between PE, SI, FC, competence, and M LMS utilization. However, EE and attitude do not affect M LMS utilization through the BI mediator. The results of the moderation effect of gender on M LMS utilization in Saudi Arabia revealed that the beta value of the male for PE, EE, and SI on M LMS utilization is significant. Moreover, the findings demonstrated that the beta value of females for FC is significant, as opposed to male FC on M LMS utilization, which is not significant. Therefore, gender has a significant moderating role in the relationship between FC and M LMS utilization. In addition, the beta value of males and females for attitude and competence is not significant. Thus, the age factor does not significantly moderate the relationship between these variables and M LMS utilization. The PE, SI, FC, and competence factors significantly influence teachers’ BI and M LMS utilization in public schools in Riyadh, KSA. The findings obtained have practical implications for educational systems in Saudi Arabia to promote the use of M LMS among school teachers. Schools should consider the existing BI of teachers before deciding whether the system is going to be utilized or not, particularly in Riyadh. Also, the findings would encourage the successful integration of M LMS into the teaching and learning process in Riyadh.